Synthesis of In2Se3 and Cu2-xSe Micro- and Nanoparticles with Microwave-Assisted Solvothermal and Aqueous Redox Reactions for the Preparation and Stabilization of Printable Precursors for a CuInSe2 Solar Cell Absorber Layer - Schuster, Matthias; Distaso, Monica; Möckel, Stefan; Künecke, Ulrike; Peukert, Wolfgang; Wellmann, Peter (Energy Procedia, 2015)
Micro- and nanoparticles were synthesized and stabilized in order to process a copper indium diselenide (CISe) solar cell absorber layer. A microwave assisted solvothermal reaction for In2Se3 particles was performed, finding that smaller particles could be obtained in shorter times and at lower temperatures than with a conventional autoclave based solvothermal synthesis. In a second route In2Se3 and Cu2-xSe nanoparticles have been synthesized via aqueous redox reactions and been Zeta potential-stabilized to acquire a nanoparticulate ink. This ink was drop cast in ambient atmosphere and annealed in N2 -atmosphere leading to the formation of CISe at lower temperatures than with state-of-the-art processing route
Keywords: In2Se3; Cu2-xSe; nanoparticles; microwave; Zeta potential; low temperature; CuInSe2; solar cell